Clinical factors associated with canine subclinical myxomatous mitral valve disease stage progression in South Korea - Yang, Isaac; Min, Kyung-Duk (Journal of Biomedical Translational Research, 2024)
Myxomatous mitral valve disease (MMVD) in dogs is a heart disease that is characterized by histopathologic changes in cardiomyocytes, which ultimately result in valve degeneration and blood regurgitation due to structural changes in the heart valves. A number of studies have been conducted with the objective of identifying prognostic factors that may influence the prognosis of dogs with MMVD. Nevertheless, there is a paucity of research examining the factors that predict MMVD stage progression as defined by the American College of Veterinary Internal Medicine. The objective of this study was to examine whether there are factors associated with stage progression within one year of diagnosis in dogs diagnosed with subclinical MMVD (stage B1 or B2) using physical examination findings, clinicopathologic biomarkers, and echocardiographic markers. This is a retrospective study of veterinary practice performed at Chungbuk National University Animal Hospital. The electronic medical record of the hospital was searched to obtain clinical records of canine patients diagnosed with subclinical MMVD over an 11-year period. For each patient cohort, a logistic regression analysis was conducted. The variables were initially selected using the backward elimination method, and the optimal logistic regression model was determined by removing the independent variables with the largest variance inflation factor. Among the independent variables examined in this study, heart murmur intensity was identified as a statistically significant predictor of stage progression within one year for subclinical MMVD, a finding that aligns with those of previous studies. No other independent variables were found to be significantly associated with subclinical MMVD stage progression. This is the inaugural exploratory study to concentrate on blood test results, a relatively straightforward and quantifiable test result that can be readily obtained in primary care veterinary clinics, among the factors that may be associated with the progression of subclinical MMVD stages.